Arabisme dalam Pandangan Islam Perspektif Kebinekaan di Indonesia - Ade Budiman (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2019)
Muslims in Indonesia are faced with the problematic understanding that emerged recently as if a handful of circles of Muslims in Indonesia is the wrong and do not understand, by not necessarily in line with the conceptionof the Unitary State of the Republic of Indonesia, so it is very unfortunate once the emergence of differences in the principle of perceiving it among the level of the Ulama, Cendikia, Umara and Indonesian Muslims itself, while the noble values and idealism in religion during the classical period in Indonesia has been a source of cultural preservation and harmony in the relations of peer relations, namely Indonesia with Unity in Diversity. The description of religious history data in the classical period in Indonesia is considered important to reconstruct the plural and multicultural society of Indonesia in the present and future. The challenge for Muslims today is to be able to sort and vote on what the state law considers and sees as good, and its rules are clear in the teachings of the Qur'an and Al-Hadith. As we all know that to become a Muslim does not mean to be the araban, because to become araban not necessarily Islam. But remember, Rasulullah SAW is an Arab and the Quran is revealed in Arabic.